Safety of UV‐treated powder of whole yellow mealworm (Tenebrio molitor larva) as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA Panel); Dominique Turck; Torsten Bohn; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Alexandre Maciuk; Inge Mangelsdorf; Harry J McArdle; Androniki Naska; Carmen Pelaez; Kristina Pentieva; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on UV‐treated powder of whole yellow mealworm (Tenebrio molitor larva) as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The term yellow mealworm refers to the larval form of the insect species T. molitor. The NF is the UV‐treated powder of the whole, thermally dried yellow mealworm. The NF consists mainly of crude protein, fat, digestible carbohydrates and fibre (chitin). The Panel notes that the levels of contaminants in the NF highly depend on the occurrence levels of these substances in the insect feed. The Panel notes furthermore that there are no safety concerns regarding the stability of the NF if the NF complies with the proposed specification limits during its entire shelf life. The NF has a high protein content, although the true protein content in the NF is overestimated when using the nitrogen‐to‐protein conversion factor of 6.25, due to the presence of non‐protein nitrogen. The applicant proposed to use the NF as an ingredient in various food products, such as bakery products, pasta, compotes of fruit/vegetables and cheese. The target population is the general population. The Panel notes that considering the composition of the NF, the proposed conditions of use and that the NF will not be the sole source of dietary protein, the consumption of the NF is not nutritionally disadvantageous. Despite the UV treatment, the Panel notes that the NF is not a significant dietary contributor of vitamin D3. The submitted toxicity studies from the literature did not raise safety concerns. The Panel considers that the consumption of the NF may induce primary sensitisation and allergic reactions to yellow mealworm proteins and may cause allergic reactions in subjects with allergies to crustaceans and dust mites. Additionally, allergens from the feed may end up in the NF. With the exception of possible allergenicity, the Panel concludes that the NF is safe under the proposed uses and use levels.